THE DEVELOPMENT OF ALGEBRA QUESTION BOOK FOR HIGH SCHOOL MATHEMATICS OLYMPIAD TRAINING - PUTERI APRILIANTI; SOMAKIM SOMAKIM; YUSUF HARTONO (Sriwijaya University Learning and Education International Conference, 2016)
The purpose of this research is to produce a Algebra question book for high schoolmathematics olympiad training that valid. This research is a development researchconsists of two stages: a preliminary stage includes the analysis and design andformative evaluation in this case just include self- evaluation , expert review, andone - to-one ,that we discuss in this paper. Question book, in the beginning wasreviewed by expert in Expert Review stage, and get comment by colleague to seehow validity the book is. After that, Question book was revised based on commentand review by validator . In One-to-one stage, Question book tested to two studentwho have average ability and high ability to know about how usage the questionbook is. Result of one-to-one stage is student’s answer, observation data, andinterview response that use to revise Question book. From these results it can beconcluded that Algebra Question book for high school mathematics olympiadtraining that develop is valid.